Morphology of two varieties of sweet corn when applied with cow dung fertilizer - Mukhlis, Ahmad; Fahri, Romi; Khairani, Siti (Contributions of Central Research Institute for Agriculture, 2024)
Sweet corn is an agricultural commodity that is very popular with the public because of its many benefits. In Indonesia, sweet corn can be used as a source of food, feed and industrial raw materials. However, the demand for sweet corn in Indonesia is high, resulting in not all needs being met. Efforts that can be made to increase sweet corn production are by using high-yielding varieties and by providing organic fertilizer which can minimize the residue effects caused by inorganic fertilizer. This research aims to determine the effect of two varieties of sweet corn on the growth and production of sweet corn, to determine the correct dose for applying cow dung compost fertilizer on the growth and production of sweet corn and to determine the interaction between two varieties of sweet corn and the dose of cow dung compost fertilizer on the growth and production of sweet corn. This research used a factorial Randomized Block Design (RBD) with 2 factors and 4 replications. The first factor is the use of two varieties of sweet corn, namely V1 (bonanza) and V2 (talenta). The second factor is the application of compost fertilizer at 3 levels, namely: P0 (without organic fertilizer), P1 (600 g/plant hole (equivalent to 12 kg/plot)), P2 (750 g/plant hole (equivalent to 15 kg/plot) ). The results of the research showed that the bonanza variety is better in growth which can be seen in the parameters of plant height, number of leaves and leaf area when compared to the talenta variety. Providing cow dung fertilizer can increase plant height, number of leaves and leaf area. A dose of 600 g/plant is the most efficient dose of cow dung fertilizer for the growth of sweet corn plants.